வள்ளுவர் காட்டும் நட்பு ( THE FRIENDSHIP THAT VALLUVAR SHOWS) - Rajoo, Arul Selvan (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2018)
This article explores about the immense values of friendship as argued by Tiruvalluvar. The remarks of Tiruvalluvar about friendship are useful, and they would be there as long as the human race exist. There is no doubt that in today’s increasingly humanized world, these ideas can be used to get away from the vagabond, free from the hassles of life, and befriend the good. Keeping these thoughts in mind for a long time, the friendship is a great place in the lives of everyone who seeks to promote friendship. ஆய்வுச் சுருக்கம் வள்ளுவரின் நட்பைப் கருத்துகள் மனித இனம் இருக்கும் வரை பயன்படக்கூடிய ஒன்றாகும். இயந்திரமயமாகிவிட்ட இன்றைய மனித வாழ்க்கையில், வஞ்சகர்டமிருந்து விலகி, வாழ்வின் தொல்லைகளிலிருந்து விடுபட்டு, நல்லவரோடு பழகி நட்புக்கொள்ள இக்கருத்துகள் பெர்தும் பயன்படும் என்பதில் எள்ளளவும் ஐயமில்லை. எக்காலத்திற்கும் ஏற்புடைய இக்கருத்துகளை மனத்தில் கொண்டு, நட்பைச் சிறப்பித்து நட்போடு வாழ முற்படும் ஒவ்வொருவரின் வாழ்விலும் நட்பு சிறந்ததோர் இடத்தைப் பெரும் என்று திண்ணமாகக் கூறலாம்.